2022
DOI: 10.3390/genes13061089
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Stickler Syndrome

Abstract: The Stickler syndromes are a group of genetic connective tissue disorders associated with an increased risk of rhegmatogenous retinal detachment, deafness, cleft palate, and premature arthritis. This review article focuses on the molecular genetics of the autosomal dominant forms of the disease. Pathogenic variants in COL2A1 causing Stickler syndrome usually result in haploinsufficiency of the protein, whereas pathogenic variants of type XI collagen more usually exert dominant negative effects. The severity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Over the past 20 years, a taxonomy of the SS subgroups based on vitreous characteristics has emerged. It has been shown that this taxonomy is a reliable strategy for both diagnosing SS and directing molecular study [11,12] . Type 3 SS is a non-ocular type of SS, manifesting as prelingual development of sensorineural hearing loss, growth of the epiphyses with generalized shortening of the limbs, and vertebral body dysplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 20 years, a taxonomy of the SS subgroups based on vitreous characteristics has emerged. It has been shown that this taxonomy is a reliable strategy for both diagnosing SS and directing molecular study [11,12] . Type 3 SS is a non-ocular type of SS, manifesting as prelingual development of sensorineural hearing loss, growth of the epiphyses with generalized shortening of the limbs, and vertebral body dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…The haploinsu ciency of COL2A1, the encoding gene for collagen type II alpha 1 chain, is responsible for autosomal dominant type 1 SS [10] . Type 2 SS (OMIM #604841), representing the remaining 10-20% of cases, is usually caused by monoallelic mutations in COL11A1 which encodes the collagen type XI alpha 1 chain [11] . However, biallelic pathogenic variants of COL11A1 have also been reported occasionally [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Stickler Syndrome as one of many syndromes associated with COL2A1 mutations, presents with a broad range of anatomical findings and ophthalmological complications, often leading to difficulty with diagnosis, treatment, and genetic counseling [ 4 ]. Recent reviews have begun to detail these varied presentations with genotype-phenotype correlations as technology continues to progress [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Autosomal dominant and recessive inheritance patterns associated with different target genes (COL2A1, COL11A1, COL11A2, COL9A1, and COL9A3) have been identified [ 1 , 3 , 5 , 6 , 7 ]. Most patients with autosomal dominant Stickler Syndrome carry one mutated collagen allele, however, there has been one reported case of biallelic heterozygosity of COL11A1 mutations which resulted in retinal atrophy and severe hearing loss [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation